A response of rituximab plus lenalidomide therapy in patients with post-transplant lymphoproliferative disease and methotrexate-related lymphoproliferative disorder in the central nervous system: a case report - Hanguo Guo; Hong Zhang; Wenyu Li (Journal of Medical Case Reports)
Abstract Background Post-transplant lymphoproliferative disorder and methotrexate-related lymphoproliferative disorder are rare complications normally with unfavorable prognosis. Post-transplant lymphoproliferative disorder of the central nervous system is a rare disorder and predominantly presents as diffuse large B-cell lymphomas of non-germinal center cell origin. However, the treatment for these patients with this diagnosis has not reached a consensus. Case 1 and 2 presentations In this case report, one patient with post-transplant lymphoproliferative disorder and another patient with methotrexate-related lymphoproliferative disorder were both diagnosed with Epstein–Barr virus–diffuse large B-cell lymphomas of primary central nervous system. The former case was a 37-year-old Han Chinese female diagnosed with post-transplant lymphoproliferative disorder of the central nervous system after a kidney transplant, and the latter case was a 61-year-old Han Chinese male diagnosed with methotrexate-related lymphoproliferative disorder after receiving methotrexate treatment for psoriasis. The initial treatment for both of them was rituximab plus lenalidomide followed by lenalidomide as maintenance for disease progression or intolerance. After the treatment, magnetic resonance imaging showed partial response or complete remission of their brain lesions. In addition, the renal function of the patient with post-transplant lymphoproliferative disorder of the central nervous system was normal, and psoriasis did not recur in the patient with methotrexate-related lymphoproliferative disorder during lenalidomide maintenance treatment. Conclusion The treatment has proved to be a promising therapeutic method for post-transplant lymphoproliferative disorder of the central nervous system and methotrexate-related lymphoproliferative disorder, when the decreasing or withdrawal of immunosuppressive therapy could not achieve a satisfying outcome. Owing to the relatively small sample size, the effect of this treatment should be further investigated under a larger sample size.